Pengaruh persentase lemak tubuh terhadap kapasitas aerobik atlet sepak bola profesional - Syania Shabrina; Dhoni Akbar Ghozali; Dwi Rahayu (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
Football is a high-intensity sport with a wide variety of movements. Football athletes, especially professional athletes, must have the optimal aerobic capacity (VO2 Max) to achieve best performance in every match. One of the factors that influences VO2 Max is body fat percentage. The aim of this study was to examine the effect of body fat percentage on maximal aerobic capacity in Indonesian professional football athletes. This research is an analytical cross-sectional study with the data collection method from tests and measurement. The population in this study was football players of Bhayangkara Football Club that participated in Liga 1 Indonesia 2021/2022. The research was conducted among 27 players that were taken by the saturated sampling method. The body fat percentage was measured using skinfold thickness Jackson Pollock 7 sites. The VO2 Max was determined by Yo-Yo Intermittent Recovery Test Level 2. The result showed a negative correlation between body fat percentage and VO2 Max (p = 0,042). It points out that body fat percentage has an effect on maximal aerobic capacity; the lower body fat percentage, the higher aerobic capacity of professional football players.